Efektifitas Pembayangan yang dihasilkan Pohon dan Bangunan di Koridor Jalan Perkotaan Untuk Mencapai Kenyamanan Termal - Jockie Zudhy Fibrianto; Mochamad Hilmy (EMARA: Indonesian Journal of Architecture, 2018)
The road corridor in Pontianak City has different shading output depending on the sun orientation. The difference has caused a temperature difference that affects the pedestrian thermal comfort along the corridor. Identification and measurement of shading temperatures that occur due to buildings and trees were carried out for three days in each afternoon with relatively similar weather conditions. The road corridor that becomes the research location was at A. Yani St.-Gajah Mada St.-Tanjung Pura St., which has a North-South orientation and Teuku Umar St.-Diponegoro St.-Sisingamangaraja St., who has an East-West direction. The analysis phase is done by comparing the effectiveness of imagery produced by buildings and trees. After that, the identification and measurement results are compared with Indonesian thermal comfort standards SNI T-14-1993-03 to obtain suitable thermal comfort in the road corridors in Pontianak City.